Spillover Implications of China's Slowdown for International Trade - Blagrave, Patrick (Spillover Notes; Spillover Notes ;, 2016)
Using a panel vector autoregression and a novel measure of export-intensity-adjusted final demand, this note studies spillovers from China's economic transition on export growth in 46 advanced and emerging market economies. The analysis suggests that a 1 percentage point shock to China's final demand growth reduces the average country's export growth by 0.1-0.2 percentage point. The impact is largest in Emerging Asia, where an export-growth-accounting exercise suggests that China's economic transition has reduced average export growth rates by 1 percentage point since early 2014. Other countries linked to China's manufacturing sector, as well as commodity exporters, are also significantly affected. This suggests that trading partners need to adjust to an environment of weaker external demand as China completes its transition to a more sustainable growth model.